Measuring Illuminance Level Based on Wall’s Colour - MASLIZAM, MUHAMMAD MIRZA; Abdul Hafiz, Deena Batrisyia; Mohd Hanafiah, Nur Diyana; Abd Kadir, Aslila (Multidisciplinary Applied Research and Innovation, 2023)
The title of this study is to measure the level of lighting based on the color of the walls. This study will evaluate the lighting quality of the wall color in Pagoh residential college, UTHM, Johor and at different times. The objective used is to understand the concept of natural lighting in a building. Also, to measure the level of illumination with different wall colors. And to compare the brightness of each color. In addition, the method used to complete this project is the construction of a 1:10 scale model of the building, the measurement of the lighting level was made through the use of a lux meter and observations were made for three days. The importance of this study has been identified which is the suitability of wall color to a building space. In this regard, the findings show that the measurement of the level of lighting is very important to know the effect of wall color on the quality of lighting. Next, be able to identify the appropriate color to produce good lighting in the building space. In conclusion, from this final year project gives useful knowledge to the future community to select the suitable wall colors based on illuminance level.